Characterization of Banana Peel Corrosion Inhibitor by Vacuum Microwave Assisted Extraction (VMAE) Method in 2% HCl Environment - binti Jamaluddin, Jamarosliza; Paramitha, Tifa; Salsabila, Iva Najwa; Luviana, Angely; Ramadhan, Muhammad Zikri; Putri, Angelina; Nurbaits, Alisya; Sihombing, Rony Pasonang (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
Banana peel is a waste that is very abundant in Indonesia. The utilization of banana peel can be used for corrosion inhibitors. The type of environment applied in this study is an acidic environment, which is carried out in 2% HCl solution media. The purpose of this study is utilize banana waste extract obtained from the VMAE method. The extract was obtained by VMAE method at 150 watts, 300 watts and 450 watts for 10 minutes using ethanol solvent. The ratio of feed and solvent used was 1:10 (b/v). The results of the extract were subjected to phytochemical tests using Dragendroff, Wagner and Mayer reagents. After that, the extract was applied to the media for corrosion rate test and GC-MS. The results of the study showed that the lowest corrosion rate was obtained at a concentration of 1500 ppm non-aerated which was 0.7347 mmpy. While based on the GC-MS test results, terpenoid compounds and vitamin E can be detected from banana peel extract, where these two compounds are antioxidant substances that can be utilized as corrosion inhibitors.